Exploring digital libraries foundations, practice, prospects - Calhoun, Karen (London : Facet Publishing, c2014.)
Teh emergancy of digiral libraries in the early 1990s was a critical turning point in the shift to networked information. Calhoun examines the foundations, current practice and prospects of digital libraries, and explores the possibiliteis of a shift toward a community-centered perspective based on what digital libraries contribute of might contribute in a time of societal change
Glossary - - Emergence and definitions of digital librareis -- Outcomes of digital libraries' first decase -- key themes and challenges in digital libraries -- Digital library collectios : repositories -- Hybrid libraries -- Social roles of digital libraries -- Digital libraries and their communities -- The prospects of open access repositories -- Dogotal libraries and the social web : scholarship -- Digittal libraries and the social web : collections and patforms
Includes bibliographical references (pages 257-309) and index
Keywords: Digital libraries; Libraries -- Special collections -- Electronic information resources